Pengaruh Kepedulian Orang Tua Terhadap Perkembangan Kognitif Anak Berdasarkan Analisis Pola Pengasuhan - Rosi Rosyani; Heri Yusuf Muslihin; Taopik Rahman (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2022)
Early childhood development needs to be considered properly, especially cognitive development. However, there are still many parents who are less sensitive to this. Therefore, the authors conducted a study to determine the level of parental concern for the cognitive development of children who were analyzed based on parenting patterns. The research method used a survey method with a sample of 20 parents and 20 teenagers. The results show that there are 45% of parents who choose authoritative parenting and 45% of adolescents who get authoritative parenting from their parents. With this figure, parenting is very influential on children's cognitive development, some of the effects are 50% of people are easy to interact socially, 75% of people are easy to catch life's problems, 55% of people are difficult to find solutions to their problems, 60% are able to understand the concept of value/ love even though it is still difficult, and 65% feel a little involved in the learning process. The author advises readers to always apply authoritative parenting because it is included in the ideal parenting pattern.